Pengembangan Sistem Informasi Berbasis Cloud untuk Manajemen Syarat Kelulusan Siswa di Sekolah IDN Akhwat - Lestari, Sri; Pratiwi, Tiyas Aria; Az-zahra, Haura Salsabila; Paramida, Feti (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
IDN Akhwat School, as an educational institution committed to Islamic-based quality, faces challenges in managing student graduation requirements. To increase efficiency, they adopt technology by developing cloud-based information system applications. This application is designed to simplify and improve the management of graduation requirements in real time. With cloud technology, graduation requirements data can be accessed and updated quickly, enabling efficient monitoring of student progress. Easy accessibility for schools, teachers, and students via internet-connected devices provides flexibility in management. This application undergoes usability testing in the implementation phase to ensure a friendly and functional interface. Evaluation via the System Usability Scale (SUS) is used to identify potential improvements. With this development, IDN Akhwat School is expected to increase the efficiency of graduation management, strengthen information transparency, and positively contribute to Islamic-based education.